2014
DOI: 10.7763/ijapm.2014.v4.290
|View full text |Cite
|
Sign up to set email alerts
|

The ARL of EWMA Chart for Monitoring ZINB Model Using Markov Chain Approach

Abstract: Abstract-In this paper, we proposed the Markov Chain Approach (MCA) to evaluate the average run length (ARL) of exponentially weighted moving average (EWMA) control chart when zero-inflated counted are observed in a negative binomial model. Furthermore, the efficiency of the MCA is compared with Monte Carlo Simulation via the CPU times which the former is much saving computational times used when compared with the latter method.Index Terms-Exponentially weighted moving average, zero-inflated negative binomial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The performance of the stated proposal was evaluated by several measures, and results revealed that the combined EWMA structure outperformed the simultaneous EWMA structure. Further, an explicit expression for the ARL of the DMA chart based on the ZIB distribution was proposed by Areepong and Sukparungsee, and Bualuang et al, while a Markov chain approach for the ARL of CUSUM and EWMA control chart under ZIP and ZINB models was discussed in Chananet et al, Chananet et al, and Sukparungsee . A one‐sided CUSUM chart for ZIB distribution was proposed by Rakitzis et al This chart was designed to monitor increasing and decreasing shifts in the ZIB parameter p 2 , and comparative analysis was done with the Shewhart chart (cf.…”
Section: Statistical Monitoring Based On Zero‐inflated Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the stated proposal was evaluated by several measures, and results revealed that the combined EWMA structure outperformed the simultaneous EWMA structure. Further, an explicit expression for the ARL of the DMA chart based on the ZIB distribution was proposed by Areepong and Sukparungsee, and Bualuang et al, while a Markov chain approach for the ARL of CUSUM and EWMA control chart under ZIP and ZINB models was discussed in Chananet et al, Chananet et al, and Sukparungsee . A one‐sided CUSUM chart for ZIB distribution was proposed by Rakitzis et al This chart was designed to monitor increasing and decreasing shifts in the ZIB parameter p 2 , and comparative analysis was done with the Shewhart chart (cf.…”
Section: Statistical Monitoring Based On Zero‐inflated Distributionsmentioning
confidence: 99%
“…-Chananet et al, 68 Chananet et al 69 Chananet et al 68 Chananet et al 63 FIP and GIP Rakitzis et al, 78 Rakitzis et al 79 -…”
Section: Zinbmentioning
confidence: 99%
“…This type of simulation approach is employed when the mean and other measures of the proposed chart are unavailable. Several researchers of the statistical process control used the simulation approach for numerical calculations of the proposed methodology including, for example, [17].…”
Section: In-control Processmentioning
confidence: 99%
“…This simulation approach is commonly used when the exact form of the mean and other measures of the proposed process is not available. Many researchers have used the simulation approach for the effectiveness of control charts including among others Santos (2009), Abbasi and Miller (2013), , , Chananet et al (2014), Shu et al (2014), , Azam et al (2015) and Aslam (2016).…”
Section: Performance Evaluation Of the Proposed Chartmentioning
confidence: 99%